Red sings from treetops a year in colors - Sidman, Joyce; Zagarenski, Pamela (Boston Houghton Mifflin Books for Children, 2009)
The names of colors are woven into unrhymed poems that celebrate the seasons.
Keywords: Seasons -- Juvenile poetry; Colors -- Juvenile poetry; Children's poetry, American; Seasons -- Poetry; Color -- Poetry; American poetry